Kloning Genα-Amilase Pendegradasi Butir Pati dariBacillus aquimaris MKSC 6.2 pada Vektor pGEM-T - Nurul Widya (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
α-Amylase (EC 3.2.1.1) is an enzyme which hydrolyzes α-1,4 glicosidic bonds inpolysaccharides such as amylose and amylopectin. α-Amylase is widely applied in industry, such asstarch processing, detergent, and pharmaceutical industries. α-Amylase Bacillus aquimaris MKSC6.2 can degredate raw starch at low temperature, hence it has a potential economic value as analternative enzyme in starch processing. The long term goal of this research is to produce B.aquimaris α-amylase recombinant, while the short term goals of this research were to amplify thebaqA gene by PCR method and to clone the resulted DNA fragment gene in pGEM-T vector. The α-amylase gene amplified by PCR using forward primer and reverse primer has a size of 1.5 kb.Recombinant pGEM-T plasmid containing the 1.5 kb α-amylase fragment has been obtained.Keywords: raw starch,α-amylase,B. aquimarisMKSC 6.2, recombinant plasmid